Two degrees up—Part Two: Ghana - Jarvis, Andy (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2010)
Farmers in the Upper West Region of Ghana are finding that rising temperatures and increasingly unpredictable rains are compounding the long-running problems of population pressure and declining soil fertility. The CGIAR's Climate Change Research Program, led by CIAT, is seeking sustainable scientific solutions to help small farmers prepare for - and rise to the challenge of - climate change. The Two Degrees Up series of photo stories takes a closer look at the scale of the challenge ahead.